Seroprevalence of anti‐SARS‐CoV‐2 antibodies in Africa: A systematic review and meta‐analysis. (6th July 2021) - Chisale, Master R. O.; Ramazanu, Sheena; Mwale, Saul Eric; Kumwenda, Pizga; Chipeta, Mep; Kaminga, Atipatsa C.; Nkhata, Obed; Nyambalo, Billy; Chavura, Elton; Mbakaya, Balwani C.
Abstract: We estimated the seroprevalence of anti‐severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibodies in residents of African countries and explored its associated factors. We searched PubMed, EMBASE, PsycINFO, AMED, CINAHL, DOAJ and Google Scholar databases for peer reviewed articles and pre‐prints that reported anti‐SARS‐CoV‐2 antibody seroprevalence of general or specific human populations resident in Africa. The eligible studies were evaluated using Joana Briggs Institute prevalence critical appraisal tool. Twenty‐three studies involving 27, 735 individuals were included in our paper. The pooled seroprevalence of anti‐SARS‐CoV‐2 antibodies in Africa was 22% (95%CI: 14–31) with very high heterogeneity ( I 2  = 100%, p  < 0.001). Seroprevalence was highest in studies conducted in Central Africa compared to Southern Africa, West Africa, North Africa and East Africa respectively. The number of days between the first reported coronavirus disease 2019 case in each country and when a seroprevalence study was conducted was a significant moderator of seroprevalence. Seropositivity was numerically influenced by gender and age of the participants with males and those aged below 50 years being most affected with SARS‐CoV‐2 infection. The highest pooled seroprevalence in Africa reported in this review should be interpreted cautiously due to high heterogeneity between studies. Continued seroprevalence surveillance is warranted to establish Africa's transition towards herd immunity.